Sistem Informasi Akuntansi Penjualan Tenaga Listrik Tahun 2023 PT PLN ULP Genteng - Syafira Ilma Maulida; Rini Puji Astuti; Devi Kumala Sari; Hanifah Sulviana (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to analyze the electricity sales accounting information system at PT PLN (Persero) ULP Genteng, one of the customer service units under the PT PLN (Persero) UP3 Banyuwangi network service area. The focus of this research includes electricity sales during 2023 with the aim of finding out whether the accounting information system is running well. The data source used in this research is primary data, which the researcher obtained directly from the original source. This research reveals that electricity sales in 2023 will continue to increase in line with the growth of the productive age population and societal development. Customer data shows consistent increases, driven by household and business needs. So, the increase in electricity sales can be understood through internal and external factors that influence consumers and electricity needs. The benefit of this research is to provide an understanding of the role of the electricity sales accounting information system, so that it can increase the efficiency and accuracy of PT PLN (Persero) ULP Genteng's financial records.